Tomosynthesis: A new radiologic technique for rapid diagnosis of scaphoid fractures. Issue 3 (June 2018) - Compton, N.; Murphy, L.; Lyons, F.; Jones, J.; MacMahon, P.; Cashman, J.
Abstract: Scaphoid fractures constitute 71% of all carpal bone fractures. 1 Early diagnosis and treatment has significant bearing on fracture union rates and better clinical outcomes. While displaced fractures can be readily seen on plain radiograph, undisplaced fractures can require advanced imaging modalities to confirm that diagnosis. Advanced imaging such as Magnetic Resonance Imaging (MRI), Computerised tomography (CT) and bone scintigraphy are routinely used for the diagnosis of scaphoid fractures but require significant radiation exposure, increased cost and can be difficult to access. 2 Tomosynthesis is an emerging imaging modality which uses conventional x-ray systems to produce cross-sectional images. There has yet to be extensive research carried out investigating the diagnostic value of tomosynthesis in scaphoid fractures. The aim of this study is to optimise patient positioning for the diagnosis of scaphoid fractures in a cadaveric model and compare the diagnostic yield of tomography to conventional CT. Using four cadaveric specimens, three limb positions were examined in unfractured and fractured scaphoids to determine the optimal limb positions required for visualisation of the scaphoid. As a result of this study, the optimal position for visualisation of the scaphoid and diagnosis of scaphoid fractures has been determined. The results demonstrate that tomosynthesis is as effective as CT scanning in identifying scaphoid fractures in both sensitivity and specificity. By comparison to CT, tomosynthesis is cheaper, has lower radiation exposure, requires fewer hospital resources and can be performed quickly. Tomosynthesis is a valid diagnostic tool for the diagnosis of scaphoid fractures.